Pengaruh Teknik SQ4R dan Berpikir Kritis Terhadap Kemampuan Membaca Pemahaman Siswa - Purlilaiceu, Purlilaiceu; Suherman, Akhmad (Jurnal Artikula, 2020)
This research aims to know: the influence of SQ4R reading techniques on the ability to read understanding of high school students at Daar EL Falaah Regency Pandeglang. The influence of critical thinking on the ability to read understanding private high school students Daar EL Falaah District Pandeglang.The influence of interactive reading techniques and critical thinking towards the ability to read the understanding of private high school students Daae EL Falaah District Pandeglang. This research uses experimental method with design experiments by Treatment 2x2. Quantitative Data is obtained through comprehension reading ability tests and critical thinking tests. Data analysis using ANOVA 2 lanes and processed using SPSS 20 program. The results showed: there is a significant influence of the technique of reading on the ability to read the understanding of private high school students Daar EL Falaah Regency Pandeglang. It is evidenced by the acquisition of Sig. = 0.027 < 0.05 and Fh = 5.210. There is a significant influence of critical thinking about the ability to read the understanding of private high school students Daar El Falaah District Pandeglang. This is evidenced by the acquisition of Sig. = 0.000 < 0.05 and Fh = 23.188. There is a significant influence interaction of reading techniques and types of critical thinking on the ability to read the understanding of private high school students Daar El Falaah District Pandeglang. This is evidenced by the acquisition of Sig. = 0.042 > 0.05 and Fh = 4.349.